The Paradigm of Islamization of Knowledge According to SMN Al-Attas (From Islamization of Science to Islamic Science) - Mohammad Muslih; Happy Susanto; Martin Putra Perdana (University of Darussalam Gontor, Indonesia, 2021)
This article examines the idea of Islamization of knowledge as a variant of the issue of integration between science and Islam, to view the possibility of engendering to new science not only scientific but also religious, which is not only religious but scientific at once. With the framework of the philosophy of science, this study will bring the issue of Islamization of science more than just ideas and discourse but must forge it as a scientific paradigm, which is the paradigm of Islamization of Science. Therefore, the scientific paradigm is examined in advance, before it can be used as a perspective in reading Islamization of Science and also functionalize it in generating new knowledge. There are at least nine fundamental elements of the paradigm that must rediscover their competence with Islamic sciences, ranging from basic assumptions, values, studied issues, models, main concepts, methods of research, methods of analysis, the result of analysis or theory, and representation/ethnography. The success of this study became a large contribution to the intellectual movement that focuses on the engender of new science-based Islam or called by Islamic sciences.